Effect of Blood Pressure Control on the Severity of COVID-19 Patients - Nirwana E. Mangopo; Frans E. Wantania; Octavianus R. H. Umboh (Universitas Sam Ratulangi, 2022)
Abstract: Hypertension is one of the chronic conditions that cause the most mortality worldwide. As a comorbid disease, it is often found in hospitalized patients with coronavirus disease 2019 (COVID-19). Uncontrolled blood pressure was found to be independently associated with a higher risk for more adverse clinical outcomes in COVID-19 patients. This study aimed to evaluate the effect of blood pressure control on the severity of COVID-19 sufferers. This was a literature review study using three databases, namely PubMed, ClinicalKey, and Google Scholar according to the inclusion and exclusion criteria of the study. The results obtained 10 articles. Most showed the effect of blood pressure control on the severity of COVID-19 sufferers. In conclusion, uncontrolled blood pressure in COVID-19 patients with hypertension during hospitalization has an effect on mortality.Keywords: blood pressure control; hypertension; COVID-19 Â Abstrak: Hipertensi merupakan salah satu kondisi kronis penyebab mortalitas terbanyak di dunia dan menjadi penyakit penyerta yang banyak ditemukan pada pasien rawat inap dengan Coronavirus Disease 2019 (COVID-19). Tekanan darah yang tidak terkontrol ditemukan secara independen terkait dengan risiko yang lebih tinggi untuk hasil klinis yang lebih merugikan pada pasien COVID-19. Penelitian ini bertujuan untuk mengevaluasi pengaruh kontrol tekanan darah terhadap tingkat keparahan penderita COVID-19. Jenis penelitian ialah literature review. Pencarian data menggunakan tiga database yaitu PubMed, ClinicalKey, dan Google Scholar sesuai dengan kriteria inklusi dan eksklusi penelitian. Hasil penelitian mendapatkan 10 artikel. Sebagian besar menunjukkan adanya pengaruh kontrol tekanan darah terhadap tingkat keparahan penderita COVID-19. Simpulan penelitian ini ialah tekanan darah yang tidak terkontrol pada pasien COVID-19 dengan hipertensi selama rawat inap di rumah sakit memiliki pengaruh terhadap mortalitas.Kata kunci: kontrol tekanan darah; hipertensi; COVID-19